Penentuan Status Jenis Kelamin Khuntsa Musykil Dan Hukum Pernikahannya Perspektif Madzhab Syafi’i - Sholeh, khoirus; Diyaul Haqqi, Muhammad (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2025)
The handling of ambiguous genitalia cases in Indonesia has not become an issue that is addressed seriously. The large number of such cases in Indonesia tends to be neglected, eventually evolving into complex social problems. In Islamic marriage law—particularly according to the Syafi‘i School, which sets out the conditions required for a man and a woman when entering into marriage—there is no specific detailed provision regarding khuntsa, especially khuntsa musykil. One of the essential requirements for a valid marriage is the presence of a man and a woman; therefore, the marriage rights of a khuntsa musykil still require further and conclusive scholarly study. This research focuses on two main problems: (1) How is the determination of the gender status of a khuntsa musykil viewed from the perspective of the Syafi‘i School? (2) What is the legal status of the marriage of a khuntsa musykil according to the Syafi‘i School? This study is a library research that employs various literature sources by examining books, classical Islamic texts, and other relevant materials. The primary sources consist of the Qur’an, hadith, and Syafi‘i jurisprudential works such as Idhāh al-Musykil min Ahkām al-Khuntsā al-Musykil, Nihāyah al-Muhtāj ilā Sharḥ al-Minhāj, Fiqh al-Sunnah, al-Fiqh al-Islāmī wa Adillatuhu, Nihāyah al-Maṭlab fī Dirāyah al-Madhhab, and al-Fiqh al-Minhājī ‘alā Madhhab al-Imām al-Syāfi‘ī. Secondary sources include books that discuss interpretations of the Qur’an and hadith, as well as works that explain laws relating to marriage in general. The findings of this research show that determining the gender status of a khuntsa musykil from the Syafi‘i perspective can be carried out through several considerations, including examining the functional aspects of the reproductive organs. As for marriage law, the Syafi‘i School divides it into two categories: first, marriage is invalid if the individual’s gender status remains uncertain; second, marriage is considered valid if the gender status has been clearly established. However, if undesirable circumstances arise within the marriage—especially those related to gender—then the right to khiyār (option to annul) and fasakh (dissolution) may be exercised.